Pengaruh Efikasi Diri Dan Lingkungan Sekolah Terhadap Prestasi Belajar Siswa Kelas VIII SMP Negeri 6 Pematang Siantar Tahun Ajaran 2022/2023 - Ruth Laurencia Simaremare; Anggun Tiur Ida Sinaga; Anton Luvi Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to gain knowledge regarding the influence of self-efficacy and the school environment on the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was class VIII students at SMP Negeri 6 Pematang Siantar with a total of 171 students. The research sample consisted of 120 students. The sampling technique used was simple random sampling technique. The data collection technique used was a questionnaire. The results of this research state that: 1) There is a positive and significant influence of Self-Efficacy on learning achievement, this result can be seen in the t test where the t-count value of Self-Efficacy (3.218) > ttable (1.6580) which means that this variable is significant. 2) There is a positive and significant influence of the school environment on learning achievement. This result can be seen in the t test where the t value of the school environment (2.079) > ttable (1.6580) which means this variable is significant. 3) Self-Efficacy and the school environment together influence student learning achievement, this result can be seen in the F test where the Fcount value (7.372) > Ftable value (2.6821). The R Square coefficient of determination test was found to be 0.112, which means that 11.2% of the Self-Efficacy and School Environment variables influence the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar. Meanwhile, 88.8% is the influence of other variables not examined in this research such as interest in learning, peers, teacher teaching methods.